The Letters of Paul : An Introduction - Puskas, Charles B.; Reasoner, Mark (Book collections on Project MUSE., 2013)
"Working with noted Pauline scholar Mark Reasoner on this new, second edition--with more than 40 percent new and revised material--the authors have taken account of a host of diverse cultural, historical, sociorhetorical, literary, and contextual studies of recent years and critically reexamined several issues of authorship, date, historical situation, literary form, and rhetorical structure. They have addressed new and pressing issues, filled certain lacunae, and generally updated the book for a new generation of readers"--Back cover